Pengaruh Coping Stres Terhadap Motivasi Belajar Mata Pelajaran Pendidikan Agama Islam Siswa di Sekolah Menengah Pertama 2 Jombang - Hanum Aprilianingrum; Dhikrul Hakim; Anna Qomariana (Sujud: Jurnal Agama, Sosial dan Budaya, 2025)
This study aims to determine the effect of stress coping on learning motivation in Islamic Religious Education among students at State Junior High School 2 Jombang. The background of this study is based on the fact that students face academic pressure and longer study hours, making the ability to manage stress (coping stress) a crucial factor that can influence their learning motivation, particularly in Islamic Religious Education, which demands cognitive and affective understanding. This study used a quantitative approach with a survey method. The sample was drawn using a purposive sampling technique, consisting of seventh-grade students. The research instrument consisted of a questionnaire on stress coping and learning motivation, which had been tested for validity and reliability. Data analysis was performed using simple linear regression using SPSS. In this study, the researchers sampled a total of 48 respondents. The percentage of full-day students coping with stress was 73%, and the percentage related to learning motivation in religious subjects was 71%. The results showed a significant value of 0.00 > 0.05, indicating a significant effect.